Структура та поширеність поліорганної патології корів післяродового періоду - Zubkov, O.O.; Skliarov, P.M. (Scientific Messenger of LNU of Veterinary Medicine and Biotechnologies, 2017)
Among the diseases of the postpartum period, the most common are ketosis, hypo-luteolysis, subinvolution of the uterus, hypocalcemia, delayed afterbirth and endometritis. These pathologies exert the greatest influence on the further course of lactation and may even call into question the further productive use of animals. To date, there is a lot of information about these diseases separately, and very few people pay attention to the combination of ketosis-endometritis, endometritis-hypoluteolysis and ketosis-endometritis-hypoluteolysis as a polyorganis pathology. In connection with the foregoing, the aim of the work was to determine the structure and prevalence of multi-organ pathology of postpartum cows in the conditions of a particular farm.The total number of 290 cows of the postpartum period was subject to research. Of these, obstetric pathologies were detected in 230 animals (79%), including ketosis of 23 head (8%), endometritis – 38 head (13%), hypoluteolysis – 35 head (12%) and concomitant diseases: ketosis endometritis – 55 head (19%), ketosis-hypoluteolysis – 29 heads (10%), endometritis-hypoluteolysis – 29 heads (10%) and ketosis-endometritis-hypoluteolysis – 20 heads (7%).Thus, only 21% of the total herd of cows were clinically healthy, 8% ‒ had ketosis, 12% had ‒ hypolyteolysis, and 13% had ‒ endometritis. Diagnosis for diorgan pathology of endometritis-hypoluteolysis and ketosis-hypoluteolysis was established in 10%, ketosis-endometritis in 19%. The multi-organ pathology of ketosis-endometritis-hypoluteolysis was recorded in 7% of animals.